Unicorn night : sleep tight - Murray, Diana; Flowers, Luke ([Naperville, Illinois] : Sourcebooks Jabberwocky, 2022)
Unicorns settle down with their bedtime routine by brushing their manes and ensuring their horns gleam before singing their song and drifting off to dream.
On board pages.
2.1
K-3
AD510L
Keywords: Unicorns -- Juvenile fiction; Bedtime -- Juvenile fiction; Unicorns -- Fiction; Bedtime -- Fiction; Stories in rhyme; Board books